Capture by Threat - Dal Bó, Ernesto; Di Tella, Rafael (Journal of Political Economy, 2003)
We analyze a simple stochastic environment in which policy makers can be threatened by “nasty” interest groups. In the absence of these groups, the policy maker’s desire for reelection guarantees that good policies are implemented for every realization of the shock. When pressure groups can harass the policy maker, good policies will be chosen for only a subset of states of nature. Hence, honest and able leaders might implement bad policies, and needed reforms could be delayed. In order to make good policies more likely, the public will want to increase the cost of exerting pressure for “nasty groups” and provide rents to those in power. This last result can be used to explain the existence of political parties. They play a role resembling that of the supervisor in the literature on collusion in hierarchical agency. A rational public may also choose to ignore negative media reports on a politician’s personal life and, in general, elect “strong” political leaders. The prevalence of coercive methods of influence helps explain why countries may get to be governed by “inept politicians.”